Theoretical study of optical torques for aligning Ag nanorods and nanowires. (September 2015) - Liaw, Jiunn-Woei; Lo, Wei-Jiun; Lin, Wu-Chun; Kuo, Mao-Kuen
Abstract: The optical torque that is exerted on an Ag nanorod (NR) by the irradiance of a linearly polarized laser was studied theoretically. The multiple multipole method was used to calculate the induced electromagnetic field, and then the surface traction in terms of Maxwell׳s stress tensor was integrated over the NR׳s surface. The maps of surface traction on the Ag NR in two (parallel and perpendicular) modes of alignment in various wavelength regimes were discussed. The turning point between the two modes was demonstrated to coincide with the longitudinal surface plasmon resonance (LSPR) of the Ag NR. For example, the optical torques that are induced by different lasers (1064 nm, 633 nm and 532 nm) on Ag NR (with a radius 10 nm and an aspect ratio of 3) in water were analyzed to demonstrate the wavelength-dependent performance. The NR was aligned parallel and perpendicular to the polarization of the 1064 nm and 532 nm lasers, respectively. A laser with a wavelength of 633 nm, which was close to the LSPR, induced a null torque, and caused severe plasmonic heating. In contrast, over the entire spectrum, only the parallel mode of dielectric NRs was observed. The optical torque on Ag NR is two orders of magnitude greater than that of a high-k dielectric NR of equal size. For a highly elongated Ag NR (including nanowire), the perpendicular mode, rather than the parallel one, is induced even irradiated by a 1064 nm NIR laser, because its LSPR wavelength exceeds 1064 nm. Highlights: Turning point between the perpendicular and parallel modes is at the LSPR of Ag NR. The efficiency of optical torque of Ag NRs has a maximum at 1064 nm. The perpendicular mode is induced, if Ag nanowire is irradiated by NIR laser.